Multifunctional use of functional mock-up units for application in production engineering - Hauf, Dominik; Sus, Sebatian; Strahilov, Anton; Franke, Jörg (Proceedings - 2017 IEEE 15th International Conference on Industrial Informatics, INDIN 2017, 2017)
This paper describes how Functional Mock-up Units (FMUs) can be used multifunctional in production engineering applications. There are presented three different examples: Example one shows the behavior simulation of mechatronic components in Virtual Engineering (VE). The second application example describes the energy simulation of an automated production system while Virtual Commissioning (VC). The last presented use case of FMU implementation is an application after engineering phase, while real production runtime (digital twin). Additional to the application examples the methodical and historical background of the integration of FMUs is presented.
CRIS-Team Scopus Importer:2023-03-07
Keywords: afunctional mock-up interface; behavior simulation; cyber physical system; digital twin; energy simulation; mechatronic simulation